Equine chlamydiosis—An emerging infectious disease requiring a one health surveillance approach. (5th October 2017) - Taylor, K. A.; Durrheim, D.; Heller, J.; O'Rourke, B.; Hope, K.; Merritt, T.; Freeman, P.; Chicken, C.; Carrick, J.; Branley, J.; Massey, P.
Summary: Psittacosis is a rare but potentially fatal zoonosis caused by Chlamydia psittaci, an organism that is typically associated with bird contact. However C. psittaci is capable of infecting other non‐avian hosts, such as horses, sheep, cattle and goats. Stud staff and veterinarians have significant exposure to parturient animals and reproductive materials in their routine work. To investigate the zoonotic potential associated with the emergence of C. psittaci as an abortifacient agent in horses, we established a programme of joint human and animal surveillance in a sentinel horse‐breeding region in Australia. This programme comprised cross‐notification of equine cases to public health agencies, and active follow‐up of known human contacts, including stud workers, foaling staff, veterinarians and laboratory staff. We identified no confirmed cases of acute psittacosis despite intensive surveillance and testing of heavily exposed contacts; however, further work in the area is needed.